Вплив е-демократії на суспільний розвиток в Україні: теоретико-практичний підхід - Хаустова, М. Г. (НДІ ПЗІР НАПрН України, 2022)
У статті розкрито особливості запровадження е-демократії в Україні, висвітлено основні інструменти діяльності та наведено кращі практики функціонування. Показано сприйняття та готовність суспільства до переходу на е-платформу. Для досягнення поставленої в роботі мети були використані такі загальнотеоретичні методи дослідження, як аналіз, синтез, індукція, дедукція, порівняння для визначення змісту й складових поняття «е-демократія» та «е-урядування»; системний підхід для узагальнення основних методичних підходів щодо формування та сутності електронної демократії; методи позитивного і нормативного аналізу для вироблення рекомендацій з удосконалення моделі трансформації е-демократії. Та спеціальні (систематизації, абстрагування, декомпозиції) методи наукового пізнання, за допомогою яких в статті досліджено теоретичні засади цифрової економіки та здійснено критичний всебічний аналіз та систематизацію наукових і практичних підходів до трактування сутності принципів та цілей е-демократії. Зроблений висновок, що е-демократія повинна посісти гідне місце та увійти до порядку денного радикальних політичних реформ та стати складовою державного управління, особливо на етапі сьогодення в умовах військового стану. Дослідження проблеми е-демократії та е-урядування, та впровадження цих інститутів в Україні, ґрунтується на наявних у Раді Європи підходах щодо сутності, структури особливостей е-демократії та її запровадження. Підкреслюється, що складовими е-демократії є: електронний парламент, електронне законодавство, електронний суд, електронне посередництво, електронні вибори, електронний референдум, електронне голосування, електронні петиції, електронні кампанії, електронні опитування тощо. під терміном «електронна демократія» розуміється така політична система, в якій ІКТ використовуються для забезпечення виконання основних функцій демократичного процесу, зокрема: вільного доступу до суспільно важливої інформації, свободи слова, участі в публічному управлінні (як шляхом вільного обговорення, так й участі у виборах, референдумах тощо). Problem setting. The article reveals the peculiarities of the introduction of e-democracy in Ukraine, highlights the main tools of activity and gives the best practices of functioning. The perception and readiness of the society for the transition to the e-platform is shown. To achieve the goal set in the work, such general theoretical research methods as analysis, synthesis, induction, deduction, comparison were used to determine the content and components of the concepts of “e-democracy” and “e-governance”; a systematic approach to generalize the main methodological approaches to the formation and essence of electronic democracy; methods of positive and normative analysis to develop recommendations for improving the e-democracy transformation model. And special (systematization, abstraction, decomposition) methods of scientific knowledge, with the help of which the article examines the theoretical foundations of the digital economy and carries out a critical comprehensive analysis and systematization of scientific and practical approaches to the interpretation of the essence of the principles and goals of e-democracy. Analysis of recent researches and publications. Problems of democracy and involvement of the public in policymaking by means of information and communication technologies were studied by C. Armstrong, Y. Harlan, S. Coleman, D. Lathrop, D. Robinson, L. Ruma, E. Felten, S. Schacht, D. Shuler and others However, the first attempts to bring politics online were made by engineer-enthusiasts at the request of the authorities in order to invent an alternative to the outdated routine practice. Such experimental projects as “E-Politics” in Minnesota (1994) and “Online Democracy for Citizens” in Great Britain (1996) were the first to build social networks and create discussion forums. Some local authorities in the Scandinavian countries, Canada, and Great Britain promoted and supported e-democracy projects, but most of them lacked legal regulation and resource provision. Тarget of the research. The article analyzes the concept of e-democracy, e-government. The international experience and developments in the field of e-democracy are determined in order to identify positive legal developments in the field of e-democracy. The actions of the Ukrainian government and parliament in the field of promoting e-democracy in Ukraine are analyzed. The activities that need to be regulated by the Ukrainian government for the further implementation of edemocracy are identified. Article’s main body. The purpose of the article is to systematize the concepts of e-democracy and e-government, to analyze international experience in the field of e-democracy in order to introduce into the domestic legal system positive legal experience in the field of regulating democratic processes, for the further development of new legal norms in the field of e-democracy and e-government , taking into account the need to form a new holistic worldview among its citizens based on global trends in the development of law, the science of public administration, etc. It was concluded that e-democracy should occupy a worthy place and enter the agenda of radical political reforms and become a component of public administration, especially at the current stage in the conditions of martial law. The study of the problem of e-democracy and e-governance, and the implementation of these institutions in Ukraine, is based on the approaches available in the Council of Europe regarding the essence, structure, features of e-democracy and its implementation. Conclusions and prospects for the development. E-democracy cannot be considered a panacea for all problems of democracy or public communications, but it undoubtedly contributes to the development of two, at the present stage, inseparable historical projects democracy and the Internet. Therefore, e-democracy should occupy a worthy place and enter the agenda of radical political reforms and become a component of public administration, especially at the current stage in the conditions of martial law.
Keywords: е-демократія; інформаційне суспільство; урядування; громадянське суспільство; e-democracy; information society; governance; civil society